The effects of 3000-m swimming on subsequent 3-h cycling performance: implications for ultraendurance triathletes - Laursen, P. B.; Rhodes, E. C.; Langill, R. H. (European Journal of Applied Physiology, 2000)
The purpose of this study was to examine the physiological effects of 3000-m swimming on subsequent 3-h cycling time trial performance in ultraendurance triathletes. Eight highly trained ultraendurance triathletes [mean (SEM) age 34 (2) years, body fat 12.5 (0.8)%, maximum oxygen consumption 63.2 (2.1) ml · kg-1 · min-1] completed two randomly assigned trials 1 week apart. The swim/bike trial (SB) involved 3000 m of swimming [min:s 52:28 (1:48)] immediately followed by a 3-h cycling performance at a self-selected time-trial pace. The control trial (CON) consisted of an identical 3-h cycling time trial but without prior swimming. Subjects consumed an 8% carbohydrate (CHO)/electrolyte beverage during both trials at the rate of 60 g CHO · h-1 and 1 l · h-1. No significant differences were evident between CON and SB on the dependent measures (CON vs SB): power output [W˙, 222 (14) W vs 212 (13) W], heart rate [fc, 147 (5) beats · min-1 vs 143 (4) beats · min-1; %fcmax 80.0 (1.6)% vs 78.4 (1.5)%], oxygen uptake [3.10 (0.12) l · min-1 vs 2.97 (0.15) l · min-1], minute ventilation [82.5 (4.4) l · min-1 vs 77.3 (3.7) l · min-1], rating of perceived exertion [14.6 (0.4) vs 14.0 (0.1)], blood lactate [6.1 (0.5) mmol · l-1 vs 4.8 (0.5) mmol · l-1], and blood glucose [5.0 (0.2) mmol · l-1 vs 5.3 (0.1) mmol · l-1; all non-significant at the P > 0.05 level]. However, the CON respiratory exchange ratio was significantly greater than for SB [0.91 (0.01) vs 0.89 (0.01); P < 0.05], suggesting that the SB trial required a greater reliance on lipid as a fuel substrate. Hence, the main finding in the present study was that 3000 m of swimming had no significant performance effect (in terms of W˙) on subsequent 3-h cycling performance in ultraendurance triathletes.